Structural mechanisms of chaperone mediated protein disaggregation - Sousa, Rui (Frontiers in Molecular Biosciences, 2014)
The ClpB/Hsp104 and Hsp70 classes of molecular chaperones use ATP hydrolysis to dissociate protein aggregates and complexes, and move proteins through membranes. ClpB/Hsp104 are members of the AAA+ family of proteins which form ring-shaped hexamers. Loops lining the pore in the ring engage substrate proteins as extended polypeptides. Interdomain rotations and conformational changes in these loops coupled to ATP hydrolysis unfold and pull proteins through the pore. This provides a mechanism that progressively disrupts local secondary and tertiary structure in substrates, allowing these chaperones to dissociate stable aggregates such as beta-sheet rich prions or coiled coil SNARE complexes. While the ClpB/Hsp104 mechanism appears to embody a true power-stroke in which an ATP powered conformational change in one protein is directly coupled to movement or structural change in another, the mechanism of force generation by Hsp70s is distinct and less well understood. Both active power-stroke and purely passive mechanisms in which Hsp70 captures spontaneous fluctuations in a substrate have been proposed, while a third proposed mechanism--entropic pulling--may be able to generate forces larger than seen in ATP-driven molecular motors without the conformational coupling required for a power-stroke. The disaggregase activity of these chaperones is required for thermotolerance, but unrestrained protein complex/aggregate dissociation is potentially detrimental. Disaggregating chaperones are strongly auto-repressed, and are regulated by co-chaperones which recruit them to protein substrates and activate the disaggregases via mechanisms involving either sequential transfer of substrate from one chaperone to another and/or simultaneous interaction of substrate with multiple chaperones. By effectively subjecting substrates to multiple levels of selection by multiple chaperones, this may insure that these potent disaggregases are only activated in the appropriate context